2021
DOI: 10.3390/ijerph18063061
|View full text |Cite
|
Sign up to set email alerts
|

Time Effects of Supportive Interaction and Facilitator Input Variety on Treatment Adherence of Young People with Chronic Health Conditions: A Dynamic Mechanism in Mutual Aid Groups

Abstract: This study aims to examine the mechanism of how supportive interaction and facilitator input variety in mutual aid groups impact treatment adherence of young people with chronic health conditions, with consideration of time effects, which have been rarely studied in the existing literature. A stratified random sample of 391 individuals aged 12–45 years with chronic health conditions were recruited from mutual aid groups in Hong Kong and completed both the baseline and 12-month follow-up surveys. The results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Self-stigmatization, coping with stigmatization, the effectiveness of health care, and compliance with treatment are critical elements in chronic disease selfmanagement. 17 In this study, it was observed that the mean total score of the participants obtained from the chronic disease self-management scale was moderate (mean: 64.11±5.4; min: 21; max: 105). Among the sub-dimensions, self-stigmatization (mean: 20.80±4.2 min: 9 max: 33), coping with stigmatization (mean: 16.39±3.4 min: 9 max: 25), and health care effectiveness (mean: 12.73±2.7 min: 8 max: 20) were at a low level, but compliance with treatment (mean: 15.81±4.0 min: 5 max: 25) was at a medium level.…”
Section: Discussionmentioning
confidence: 64%
“…Self-stigmatization, coping with stigmatization, the effectiveness of health care, and compliance with treatment are critical elements in chronic disease selfmanagement. 17 In this study, it was observed that the mean total score of the participants obtained from the chronic disease self-management scale was moderate (mean: 64.11±5.4; min: 21; max: 105). Among the sub-dimensions, self-stigmatization (mean: 20.80±4.2 min: 9 max: 33), coping with stigmatization (mean: 16.39±3.4 min: 9 max: 25), and health care effectiveness (mean: 12.73±2.7 min: 8 max: 20) were at a low level, but compliance with treatment (mean: 15.81±4.0 min: 5 max: 25) was at a medium level.…”
Section: Discussionmentioning
confidence: 64%
“…The small improvements may be due to two possibilities: First, the relatively short time interval (12 months) of the current study; second, psychological well-being at baseline was collected after 6 months (at least) of participation in mutual aid groups, thus individuals may have already improved their well-being up to that point and the current analyses are picking up on any additional change over the next year. In previous studies, researchers asserted that the positive impact of mutual aid groups can be long-lasting, but that it takes time to develop because group members need time to establish trust and mutual aid [28,69]. To enhance the clinical relevance of the present findings, future research may set the baseline at the beginning of mutual aid groups and use a longer time to investigate the underlying mechanism of how mutual aid groups function to facilitate their members' psychological well-being.…”
Section: Contributions and Limitationsmentioning
confidence: 82%
“…Mutual aid is a kind of interactive support that occurs between people with similar concerns or problems, such as PCHC [28]. It comes in various forms, but most commonly, it consists of instrumental support (e.g., tangible service), informational support (e.g., advice), and emotional support (e.g., empathy and love) [29].…”
Section: Emotional Support Reception and Provision As Mediatorsmentioning
confidence: 99%
“…In our sample, the execution of the motor protocol combined with the possibility of meeting each other, even if virtually, led to a growing desire in the children to improve themselves, with the incentive to overcome their limits; it is plausible to say that there were also experiences of positive motor reinforcement [39], filling some initial gaps. The participants with ASD-HF integrated perfectly with the group and they protected and supported each other, creating a community that aimed to improve all participants [40]. The decision to include both children with typical development and those with high-functioning autism (ASD-HF) was based on an interest in comparing children's responses and needs related to physical activity practice and well-being.…”
Section: Discussionmentioning
confidence: 99%